2019
DOI: 10.1021/acs.analchem.9b02715
|View full text |Cite
|
Sign up to set email alerts
|

Dark-Field Microscopic Detection of Bacteria using Bacteriophage-Immobilized SiO2@AuNP Core–Shell Nanoparticles

Abstract: To replace molecular biological and immunological methods, biosensors have recently been developed for the rapid and sensitive detection of bacteria. Among a wide variety of biological materials, bacteriophages have received increasing attention as promising alternatives to antibodies in biosensor applications. Thus, we herein present a rapid and highly selective detection method for pathogenic bacteria, which combines dark-field light scattering imaging with a plasmonic biosensor system. The plasmonic biosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…. Poly(diallyl dimethylammonium chloride) or polyDADMAC is a cationic polyelectrolyte that has been used to electrostatically bind T4 phages on paper 134 , M13 phages on glass 208 , and S13' phages on gold 71 ; in the latter case for the specific detection of S. aureus.…”
Section: Electrostatic Bindingmentioning
confidence: 99%
“…. Poly(diallyl dimethylammonium chloride) or polyDADMAC is a cationic polyelectrolyte that has been used to electrostatically bind T4 phages on paper 134 , M13 phages on glass 208 , and S13' phages on gold 71 ; in the latter case for the specific detection of S. aureus.…”
Section: Electrostatic Bindingmentioning
confidence: 99%
“…Numerous conjugates attached to the target cell resulting in apparent aggregation causing strong light scattering. The authors reported Staphylococcus aureus' detection within 15 to 20 min with a detection limit of 8 × 10 4 CFU/mL [66].…”
Section: Bacteriophage Based Bioconjugatesmentioning
confidence: 98%
“…In another example, Imai and coworkers designed a plasmonic biosensor system to achieve the rapid and highly selective detection of pathogenic bacteria. [ 36 ] The stable and uniform nanoprobes were generated by the self‐assembling of AuNPs on larger SiO 2 spheres (SiO 2 @AuNPs). After the immobilization of phage S13′ on their surface, the nanoprobes specifically bound to Staphylococcus aureus through the interaction between phage S13′ and S. aureus , which greatly enhanced the light scattering intensity of S. aureus (Figure 11B).…”
Section: Single Plasmonic Nanoprobes In Cell Imagingmentioning
confidence: 99%
“…Reproduced with permission. [ 36 ] Copyright 2019, ACS. C) Microscopic images of MCF‐7 control cells (left column) and anti‐miRNA‐21 (200 n m )‐treated cells (right column) incubated with the binary system (mixed solution of AuNP‐1 (10 µL, 0.28 n m ) and AuNP‐2 (10 µL, 0.28 n m )) for 24 h, from up to down: bright‐field images, DFM images, Cy5 fluorescence images.…”
Section: Single Plasmonic Nanoprobes In Cell Imagingmentioning
confidence: 99%
See 1 more Smart Citation